Xuebijing injection combined with antibiotics for severe pneumonia: A meta analysis of randomized clinical trials - Long-Xun Zhu; Lian Tang; Pan-Feng Feng (Elsevier, 2022)
Background: Pneumonia is a common infectious disease. Severe pneumonia not only has common clinical features of pneumonia, but also has symptoms such as system involvement and respiratory failure, and its mortality rate ranks first among infectious diseases. The effect of antibiotic treatment on the patient alone is not good, and the symptom improvement is not significant. Numerous clinical studies have evaluated the performance of Xuebijing injection combined with antibiotics in the treatment of severe pneumonia in China. Purpose: The present meta-analysis aimed to determine the efficacy and safety of Xuebijing injection combined with antibiotics for the treatment of patients with severe pneumonia. Methods: The search strategies were performed in 6 databases (Pubmed/Meadline, Embase, Cochrane library, Web of science, China National Knowledge Infrastructure, Chinese BioMedical Database, WanFang Database) from inception to August 2021. The documents were screened and extracted according to the inclusion and exclusion criteria. Meta-analysis and Revman 5.3 were used to evaluate the quality. The meta analysis included 26 studies, totaling 2155 patients. Results: Results showed that the effective rate of Xuebijing combined with antibiotics group was higher than that of the control group [Risk Ratio (RR)=1.26, 95% confidence interval (CI): (1.21, 1.31), p < 0.001]. White blood cell (WBC) was lower [Std. Mean Difference (SMD) = -0.89, 95% CI: (-0.99, -0.78), p < 0.001], C-reactive protein level (CRP) was lower [SMD= -0.91, 95% CI: (-1.01, -0.80), p < 0.001], Clinical pulmonary infection score (CPIS) [SMD= -1.02, 95% CI: (-1.26, -0.79), p < 0.001], Procalcitonin (PCT) [SMD= -1.53, 95% CI: (-1.76, -1.29), p < 0.001], PaO2 was higher [SMD= 0.84, 95% CI: (0.70, 0.99), p < 0.001], SaO2 was higher [SMD= 0.68, 95% CI: (0.45, 0.91), p < 0.001], PaCO2 was lower [SMD=-1.07, 95% CI: (-1.29, -0.86), p < 0.001], Temperature was lower [SMD= -0.72, 95% CI: (-0.87, -0.56), p < 0.001], recovery time was lower with statistical difference. Conclusions: The present meta-analysis demonstrated that, compared with the effects of antibiotics treatment, Xuebijing injection combined with antibiotics improved the effective rate, WBC, CRP, CPIS, PCT, PaO2 and SaO2 and decreased PaCO2 and recovery time.